A Laboratory Approach for Determining Effects of Potential Oil Spillage on Water Quality of Sundarbans Mangrove Forest, Bangladesh - Ara, H; Rahaman, MS; Islam, MM; Mallick, A; Hossain, MS (Journal of Life and Earth Science, 2011)
This study was conducted in laboratory as a microcosm approach in order to know the effect of oil (diesel) spillage on water quality of Sundarbans Mangrove Forest (SMF), Bangladesh. A series of laboratory tanks were filled with water of SMF with different concentrations of oils dispersed onto the waters. The water quality parameters viz. alkalinity, free CO2, dissolved oxygen, chemical oxygen demand, hardness, major anions (sulfate and chloride) and major cations (Na+, K+, Ca+2 and Mg+2) were determined three times at nearly weekly intervals. Results indicate the degradation of oil followed by reduction of dissolved oxygen and evolution of free CO2, coupled with depletion of the concentration of Ca2+ and Mg2+ in tank waters. This might be due the complex formation of Ca2+ and Mg2+ with hydrocarbons which were insoluble in water. The water quality parameters of different laboratory tanks were also compared with those of different locations of SMF determined before the microcosm approach, suggesting that oil spillage deteriorates the water quality of SMF. Key words: Water quality; simulation; oil spillage; Sundarbans Mangrove Forest (SRF) DOI: 10.3329/jles.v3i0.7441 J. Life Earth Sci., Vols. 3-4: 23-28, 2009